1994
DOI: 10.1207/s15327752jpa6302_8
|View full text |Cite
|
Sign up to set email alerts
|

Item Level Improvements for Use of the MMPI With Adolescents

Abstract: The decision to develop a separate adolescent form of the Minnesota Multiphasic Personality Inventory (i.e., the MMPI-A) raised questions about continued use of 20 original items that seemed unnecessarily ambiguous in content when employed with younger students (Ss). The responses of 362 academically gifted boys, aged 14 to 17 years, from an urban Catholic high school were compared on the experimental 704-item Form TX of the MMPI and a form containing 20 rewritten and 9 control items. The psychometric properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition to the 58 standard scale item deletions, mostly concentrated in Scales F, 5 (Mf), and 0 (Si), the wording of 70 items was modified in an attempt to eliminate outdated or sexist language, improve awkward phrasing, increase item clarity, or make items more relevant to adolescents' life experiences (Archer, 1997;Butcher et al, 1992). Archer and Gordon (1994) and Williams, Ben-Porath, and Hevern (1994) subsequently demonstrated that the psychometric characteristics of these rewritten items were equivalent to those of the items in their original form.…”
mentioning
confidence: 96%
“…In addition to the 58 standard scale item deletions, mostly concentrated in Scales F, 5 (Mf), and 0 (Si), the wording of 70 items was modified in an attempt to eliminate outdated or sexist language, improve awkward phrasing, increase item clarity, or make items more relevant to adolescents' life experiences (Archer, 1997;Butcher et al, 1992). Archer and Gordon (1994) and Williams, Ben-Porath, and Hevern (1994) subsequently demonstrated that the psychometric characteristics of these rewritten items were equivalent to those of the items in their original form.…”
mentioning
confidence: 96%
“…Participants were excluded based on the following criteria derived from a review of procedures used in other adolescent MMPI studies (i.e., Archer & Klinefelter, 1992;Williams, Ben-Porath, & Hevern, 1994;Wrobel & Lachar, 1992) and Archer's (1992Archer's ( , 1997 MMPI-A interpretation guidelines: IQ Ͻ 70, MMPI-A scores of Cannot Say (CS) scale Ͼ 10, and T-score elevations on scales L Ͼ 80, K Ͼ 80, and F Ͼ 90. Participants were excluded based on the following criteria derived from a review of procedures used in other adolescent MMPI studies (i.e., Archer & Klinefelter, 1992;Williams, Ben-Porath, & Hevern, 1994;Wrobel & Lachar, 1992) and Archer's (1992Archer's ( , 1997 MMPI-A interpretation guidelines: IQ Ͻ 70, MMPI-A scores of Cannot Say (CS) scale Ͼ 10, and T-score elevations on scales L Ͼ 80, K Ͼ 80, and F Ͼ 90.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the MMPI-A, item changes were evaluated in a field study. Adolescents from a private school served as “project consultants”—they were given alternative wording of cumbersome items and asked to determine the readability and acceptability of the item changes (Williams, Ben-Porath, & Hevern, 1991).…”
Section: Principles Of Test Revisionmentioning
confidence: 99%